INVESTIGATION OF LIGNIN NANOCAPSULES UPTAKE IN PLANTS - Cheli, Franco (My University, 2021)
The interest of the scientific community in nanotechnology has been growing significantly in the last decades, resulting in the development of new nanomaterials and nanoparticles which can find a wide variety of applications, ranging from materials science to biomedicine. Researchers have recently started to investigate the engineering of nanoparticles which can be used as pest controls or cargo deliverers to improve agriculture yield and to reduce the use of pesticides and fertilizers in favour of more sustainable approaches. The present work aims to contribute to the advancement of nanotechnology in the context of sustainable agriculture by evaluating the viability of lignin nanocapsules (NCs) produced by ultrasonication as nanovectors (NVs) for bio-active compounds in plants. Different light microscopy and electron microscopy techniques have been used to image the roots of Eruca sativa, Eragrostis tef and Arabidopsis thaliana seedlings exposed to the NCs in several experiments which investigated the toxicity and uptake extent of the particles. The study revealed that low dilutions of the raw NCs emulsion have toxic effects on roots cells and hair and required the administration of highly diluted emulsions to avoid detrimental effects. However, the imaging revealed no evidence of NCs uptake and internalization in lively cells in any of the conducted experiments. As a consequence, we can assert that the main reason for the missed uptake must reside in the size of the particles, revealing the necessity of developing a different production process which could yield smaller particles.
Keywords: agriculture, lignin, microscopy, nanocapsules, nanomaterials, nanoparticles, nanotechnology